RELATIONSHIP BETWEEN UZBEKISTAN AND AFGHANISTAN - Yakubova Hilola Abdumurot kizi (Scholar Express Journals, 2023)
In this article, practical actions have been taken to achieve positive results in the economic, political and social spheres of the Republic of Uzbekistan and Afghanistan. As the most powerful country in Central Asia and one of Afghanistan's northern neighbors, Uzbekistan has had political ties with Afghanistan since its independence in 1991, with the exception of other periods (civil wars between jihadist organizations in the first half of the 1990s). stages of history. In the three decades of relations with Afghanistan, this country has taken a neutral side. Uzbekistan is a model that has chosen pragmatism, state-state relations, active diplomacy and mediation in its conflict with Afghanistan. In the late 1990s, the country introduced innovative plans for the 6+2 and 6+3 contact groups in 2008. Also, in the last few years, this country has shown a great interest in conducting intra-Afghan negotiations.
Keywords: Afghanistan; Uzbekistan; Pragmatism